Investigating the Optimization of Magnetic Biochar Production from Rubber Seed Shells for Enhanced Cr(VI) Removal Efficiency - Prangmoo, Yasumin; Choolaaied, Orasa; Phanchindawan, Naree; Limmun, Warunee; Chungcharoen, Thatchapol (My University, 2024)
This study aimed to utilize agricultural and produce low-cost magnetic biochar from rubber-seed shells using ferric chloride (FeCl3) as a transition metal. The study employs Response Surface Methodology (RSM) based on the Box-Behnken Design (BBD) to determine optimal production conditions for removing chromium (Cr(VI)). The effect of preparation conditions such as pyrolysis temperature (500-700 °C), duration (90-180 min), and impregnation (1-3 M) on the produced magnetic biochar was examined. The optimal condition was demonstrated based on yield percentage and Cr(VI) removal efficiencies. The study revealed that the optimal conditions for producing magnetic biochar from rubber seed shells were a pyrolysis temperature of 580 °C, a pyrolysis time of 130 min, and a FeCl3 concentration of 3 M. Under these conditions, a yield of 48.63% was achieved, and the removal efficiencies for Cr(VI) were 41.29%. This research suggests that utilizing agricultural waste products from rubber seed shells may be a viable and economical method for producing magnetic biochar, which can serve as an efficient adsorption agent.